2022
DOI: 10.1182/blood.2022015423
|View full text |Cite
|
Sign up to set email alerts
|

Response-adapted anti-PD-1–based salvage therapy for Hodgkin lymphoma with nivolumab alone or in combination with ICE

Abstract: This phase 2 trial evaluated PET-adapted nivolumab (Nivo) alone or in combination with ifosfamide, carboplatin, and etoposide (NICE) as first salvage therapy and bridge to autologous hematopoietic cell transplantation (AHCT) in relapsed/refractory (RR) classical Hodgkin lymphoma (cHL). Patients with RR cHL received 240mg Nivo every 2 weeks for up to 6 cycles (C). Patients in complete response (CR) after C6 proceeded to AHCT, while patients with progressive disease (PD) at any point or not in CR after C6 receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 57 publications
2
65
0
3
Order By: Relevance
“…Thus, most of the patients were able to proceed to autoHCT with nivo alone. The remaining seven patients received NICE, and 100% responded, with six patients achieving a CR (86%) and 1 PR (14%); 33 patients proceeded to autoHCT directly after protocol therapy, and the 2-year post-autoHCT OS and PFS were 97% and 94%, respectively [ 36 ].…”
Section: What Is the Optimal Second-line Therapy?mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, most of the patients were able to proceed to autoHCT with nivo alone. The remaining seven patients received NICE, and 100% responded, with six patients achieving a CR (86%) and 1 PR (14%); 33 patients proceeded to autoHCT directly after protocol therapy, and the 2-year post-autoHCT OS and PFS were 97% and 94%, respectively [ 36 ].…”
Section: What Is the Optimal Second-line Therapy?mentioning
confidence: 99%
“…For instance, 5-year follow-up of BV monotherapy found that 9% of patients achieved a long-term remission exceeding 5 years with no further therapy [ 27 ]. In the case of the CPI, both nivo and pembro were found to have 5-year PFS under 20% [ 38 , 39 ]; of the four patients who achieved CR with nivo in the nivo + ICE trial who refused autoHCT, three had relapsed [ 36 ].…”
Section: What Is the Optimal Second-line Therapy?mentioning
confidence: 99%
“…On the other hand, the investigation of anti-PD-1 mAb in the first relapse in several phase II studies has demonstrated increased depth of response both as a single agent and as combination therapy ( Table 1 ) [ 33 , 34 , 35 ]. Combination BV and Nivo demonstrated ORR of 82–85% and CR of 59–67% [ 32 , 69 , 70 ] At 3 year follow-up after combination achieved a PFS of 77%, and in patients who responded to induction and proceeded to ASCT, PFS improved to 91% [ 33 ].…”
Section: Immunotherapy As First Salvage and Bridge To Asctmentioning
confidence: 99%
“…In a small phase II PET-adapted study evaluating nivolumab monotherapy followed by escalation to nivolumab with ifosfamide, carboplatin, and etoposide (ICE) in patients with positive interim PET scans, 71% of patients achieved CR to the single agent nivolumab and were eligible to proceed directly to ASCT, sparing 26 of the total 42 evaluable patients from requiring cytotoxic treatments prior to ASCT. A total of 9 of the 42 patients required escalation of their treatment to N-ICE, and of these, 89% achieved CR [ 35 ]. This approach demonstrated overall 2 year PFS and OS of 72% and 95%, respectively ( Table 1 ) [ 35 ].…”
Section: Immunotherapy As First Salvage and Bridge To Asctmentioning
confidence: 99%
See 1 more Smart Citation